The Christmas countdown - Cassidy, Holly (G. P. Putnam's Sons, 2024)
"A charming holiday rom-com about a young, recently heartbroken woman who is tasked by her sister to complete Advent calendar challenges in the lead up to Christmas to reignite her belief in herself, the holidays, and love again"--